Defective Fibrinolytic Response in Atherosclerotic Patients – Effect of lloprost and Its Possible Mechanism of Action - Bertelé, Vittorio; Mussoni, Luciana; Rosso, Gianfranco del; Pintucci, Giuseppe; Carriero, Maria Rita; Merati, Maria Grazia; Libretti, Arnaldo; Gaetano, Giovanni de (Thrombosis and Haemostasis, 1988)
Plasma fibrinolytic activity and tissue-type plasminogen activator (t-PA) were defective in response to venous stasis in five out of ten patients with peripheral occlusive artery disease. Discontinuous infusions of iloprost, a stable synthetic analogue of prostacyclin, restored a normal fibrinolytic response in all five patients but did not induce a parallel increase of plasma t-PA. These findings suggest that in addition to the possible benefits due to its vasodilatory and antiplatelet activity, iloprost may improve the fibrinolytic activity in patients with atherosclerotic disease, providing them with further antithrombotic protection. The profibrinolytic effect of iloprost seems not to depend on its ability to induce vascular t-PA release. Rather, it might be related to its inhibitory effect on PAI release from platelets, endothelial cells and/or hepatocytes. Venous occlusion test represents an easy diagnostic approach to fibrinolytic defects, even if related to arterial disease, and may help select patients who need therapeutic intervention.
Keywords: Peripheral artery disease; Fibrinolytic activity (response); Prostacyclin analogues